The 'Big Dipper': the nature of the extreme variability of the AGN SDSS J2232−0806. Issue 2 (20th February 2019) - Kynoch, Daniel; Ward, Martin J; Lawrence, Andy; Bruce, Alastair G; Landt, Hermine; MacLeod, Chelsea L
Abstract: SDSS J2232−0806 (the 'Big Dipper') has been identified as a 'slow-blue nuclear hypervariable': a galaxy with no previously known active nucleus, blue colours, and large-amplitude brightness evolution occurring on a time-scale of years. Subsequent observations have shown that this source does indeed contain an active galactic nucleus (AGN). Our optical photometric and spectroscopic monitoring campaign has recorded one major dimming event (and subsequent rise) over a period of around 4 yr; there is also evidence of previous events consistent with this in archival data recorded over the last 20 yr. Here we report an analysis of the 11 optical spectra obtained to date and we assemble a multiwavelength data set including infrared, ultraviolet, and X-ray observations. We find that an intrinsic change in the luminosity is the most favoured explanation of the observations, based on a comparison of continuum and line variability and the apparent lagged response of the hot dust. This source, along with several other recently discovered 'changing-look' objects, demonstrate that AGNs can exhibit large-amplitude luminosity changes on time-scales much shorter than those predicted by standard thin accretion disc models.